2011
DOI: 10.1080/1070289x.2011.654104
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Work, Shame, and Post-Soviet Women Entrepreneurs: Negotiating Ideals of Gender and Labor in a Global Economy

Abstract: Drawing on ethnographic research among Russian women traders or "shuttle traders" (chelnoki), I examine discourses on shame as a type of emotion work and consider links to ideal gender roles among Russian women entrepreneurs. In a post-Soviet era increasingly shaped by transnational mobility, as well as by a persistent legacy of Soviet sensibilities, a focus on emotion among women traders provides an ideal lens for considering what travels between eras marked by distinct ideologies, between nation-states, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The purpose of the present study was to analyze the relationships between personality traits distinguished in the Five-Factor Model and emotional labor, work engagement and satisfaction derived from the work in services. Another argument which should be taken into consideration, is the fact that studies focusing on the above variables, and especially on emotional labor, have been rarely conducted in cultural zones outside the United States [21,22], whereas cross-national research has shown interesting differences between Western and Eastern service workers. For instance, display rules related to anger, IJOMEH 2016;29(5) 769 feelings -suppressing negative or adverse emotions, restraining expression of the true feelings or concealing one's emotions.…”
Section: Emotional Labormentioning
confidence: 99%
“…The purpose of the present study was to analyze the relationships between personality traits distinguished in the Five-Factor Model and emotional labor, work engagement and satisfaction derived from the work in services. Another argument which should be taken into consideration, is the fact that studies focusing on the above variables, and especially on emotional labor, have been rarely conducted in cultural zones outside the United States [21,22], whereas cross-national research has shown interesting differences between Western and Eastern service workers. For instance, display rules related to anger, IJOMEH 2016;29(5) 769 feelings -suppressing negative or adverse emotions, restraining expression of the true feelings or concealing one's emotions.…”
Section: Emotional Labormentioning
confidence: 99%
“…There is a thin line between engaging in sex work and migrant women using, or being expected to use, their sexuality as a currency in the labour market. Existing research has revealed sexual exchanges between migrant women from post-Soviet countries and their 'business partners' in the context of the suitcase trade (Yükseker 2004;Bloch 2011). However, less has been written about sexualized work by other migrant groups, such as African migrant women, or on sexual exchanges among migrants.…”
Section: Limits Of Labour Market Participationmentioning
confidence: 99%
“…This has been a critical task in theorising difference, divergence, the re-and-deconstruction of political, economic and social systems of governance, in the imagination of new forms of organisation. 12 Within this historicity, quite disappointingly, the 'post' prefix in 'post-socialism' came to connote the valorisation of privatisation, liberalisation, deregulation and a total transition to a market economy within a capitalist context. The rejection of the previous political order often brought a sense of nostalgia and dismay, a melancholic mood of a lost world and the despair of no alternative to the catastrophic forces of capitalism with the collapse of alternative political frameworks.…”
Section: Introduction: the Post-socialist Condition In A Context Of Cmentioning
confidence: 99%